Multifidus Muscle Changes After Back Injury Are Characterized by Structural Remodeling of Muscle, Adipose and Connective Tissue, but Not Muscle Atrophy. Issue 14 (15th July 2015) - Hodges, Paul W.; James, Gregory; Blomster, Linda; Hall, Leanne; Schmid, Annina; Shu, Cindy; Little, Chris; Melrose, James
<x xml:space="preserve">Abstract</x> Study Design. Longitudinal case-controlled animal study. Objective. To investigate putative cellular mechanisms to explain structural changes in muscle and adipose and connective tissues of the back muscles after intervertebral disc (IVD) injury. Summary of Background Data. Structural back muscle changes are ubiquitous with back pain/injury and considered relevant for outcome, but their exact nature, time course, and cellular mechanisms remain elusive. We used an animal model that produces phenotypic back muscle changes after IVD injury to study these issues at the cellular/molecular level. Methods. Multifidus muscle was harvested from both sides of the spine at L1–L2 and L3–L4 IVDs in 27 castrated male sheep at 3 (n = 10) or 6 (n = 17) months after a surgical anterolateral IVD injury at both levels. Ten control sheep underwent no surgery (3 mo, n = 4; 6 mo, n = 6). Tissue was harvested at L4 for histological analysis of cross-sectional area of muscle and adipose and connective tissue (whole muscle), plus immunohistochemistry to identify proportion and cross-sectional area of individual muscle fiber types in the deepest fascicle. Quantitative polymerase chain reaction measured gene expression of typical cytokines/signaling molecules at L2. Results. Contrary to predictions, there was no multifidus muscle atrophy (whole muscle or individual fiber). There was increased adipose and connective tissue (fibrotic proliferation) cross-sectional area and slow-to-fast muscle fiber transition at 6 but not 3 months. Within the multifidus muscle, increases in the expression of several cytokines (tumor necrosis factor α and interleukin-1β) and molecules that signal trophic/atrophic processes for the 3 tissue types (e.g., growth factor pathway [IGF-1, PI3k, Akt1, mTOR], potent tissue modifiers [calcineurin, PCG-1α, and myostatin]) were present. Conclusion. This study provides cellular evidence that refutes the presence of multifidus muscle atrophy accompanying IVD degeneration at this intermediate time point. Instead, adipose/connective tissue increased in parallel with the expression of the genes that provide putative mechanisms for multifidus structural remodeling. This provides novel targets for pharmacological and physical interventions. Level of Evidence: N/A